Efficacy of Lazolex® Gel in the Treatment of Herpes Simplex Mucocutaneous Infections and the Prevention of Recurrences: A Pilot Study - Tina A. Kituashvili; Vakhtang G. Kvirkvelia; George G. Galdava; Nino G. Archvadze (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Previous in vitro and in vivo studies indicated that walnut extract has a therapeutic effect on herpes simplex infections. This study aimed to evaluate the efficacy and tolerance of Lazolex® Gel (Iveriapharma, Tbilisi, Georgia), an emollient gel to treat mucocutaneous lesions caused by herpes simplex virus. Methods. A single-center, single-arm, open-label, phase II clinical trial was conducted with 30 patients divided into two groups: 15 patients with herpes simplex virus type 1 (HSV-1) infections and 15 with herpes simplex virus type 2 (HSV-2). All received topical treatment with Lazolex® Gel four times a day for 10 days. The efficacy and tolerance of the treatment were evaluated on day 10 and day 20 of the study. Recurrence rates were also evaluated both prior to treatment with Lazolex® and over a 4-year follow-up period subsequent to treatment. Results. The median effective time to resolution of symptoms (itching, burning, and pain) was 1.97 days in the HSV-1 group and 3.11 days in the HSV-2 group. The median effective time for vesicles and erosion to disappear was 3.64 days in the HSV-1 group and 3.88 days for the HSV-2 group. Finally, the median effective time for inflammatory signs to disappear was 5.70 and 4.32 days, respectively. Following treatment with Lazolex® Gel, the frequency of outbreaks decreased from a median of 2.00 and 1.00 times per year in the HSV-1 and HSV-2 cohorts to 0.25 and 0.00 (p=0.001 and p=0.003), respectively. Conclusions. Topical treatment with Lazolex® Gel applied to lesions four times a day for 10 days was shown to be effective and safe in the treatment of herpes simplex mucocutaneous infections and dramatically reduced the rate of recurrence. Clinical trial was approved by Drug Agency of Ministry of Labour, Health and Social Affairs of Georgia, registration # DA Nº CT-000032, date of approval 01.10.2007.